Homeownership Credit Law Review: Study of Decision Number 352 /Pdt.Sus‐BPSK/2018/PN Mdn - Khalimah Nuraini Ridho Putri; Kelik Wardiono (Proceeding International Conference Restructuring and Transforming Law, 2023)
This study aims to find out how legal considerations are by judges in Consumer Protection Disputes Against Home Ownership Credit (KPR) Ruling Number 352 /Pdt.Sus‐BPSK/2018/PN Mdn. The author uses a research strategy known as normative juridical. The results in this study are legal considerations by judges in Decision Number 352 /Pdt.Sus‐BPSK/2018/PN Mdn in accordance with the legal arrangements regarding Home Ownership Credit, namely PBI No. 20 of 2018. The judge's decision is to grant the objection request to the decision of the Consumer Dispute Settlement Agency (BPSK) Number 033/Arbitration/2018/BPSK. Mdn. Petitioner for the whole; Cancel the Decision of the Consumer Dispute Settlement Agency (BPSK) Number 033/Arbitration/2018/BPSK. Mdn 03 May 2018 ; Sentence the Respondent to pay court fees which to date have been set at Rp. 586,000.00 (five hundred eighty six thousand rupiah).